Sporotrichosis: New developments and future prospects - Carlos, Iracilda Zeppone [UNESP] (Springer Nature, 2015)
The book presents current affairs of Sporotrichosis as emergent disease with emphasis on the potential factors associated with genetic polymorphisms in Sporothrix complex. Constitutive and inducible factors play an essential role in the response of the fungal cell to the environment as determinant in the immunopathogenicity, highlighting clinical forms of Sporotrichosis and host immunocompetence. Also, a current issue interest in zoonotic transmission showing that a cat is the animal species most affected by Sporothrix species and their importance in the involvement in the human transmission. Readers can associate parameters of experimental immune response to disease development as well as the diagnostic, prophylaxis, and therapies that can be applied in the near future.